(untitled) (Journal of Dhaka Medical College, 2010)
A study was carried out in the Department of Dermatology and Venereology, Bangabandhu Sheikh Mujib Medical University (BSMMU) for a period of six months from April to September 2007. 50 patients with exfoliative dermatitis were included in the study according to the inclusion and exclusion criteria. Biochemical changes were detected by collection of blood sample and sending it for biochemical studies. The male and female ratio was 3.17:1. The study showed that 24% patients were anaemic, 44% had raised ESR, 28% had lower serum total protein, 40% had decreased serum albumin, 10% had an altered A:G ratio, 8% had raised serum creatinine, 12% had raised blood urea, 12% had raised SGPT, 10% had raised RBS, 16% had showed decreased serum calcium, 18% had hyponatraemia, 12% had hypokalaemia and 6% had hypochloraemia. Key words: Exfoliative dermatitis; biochemical change. DOI: 10.3329/jdmc.v18i2.6272 J Dhaka Med Coll. 2009; 18(2) : 127-131